2012
DOI: 10.1111/j.1365-2559.2012.04274.x
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 and Jagged2 contribute to gastric cancer development and to glandular differentiation associated with MUC2 and MUC5AC expression

Abstract: The expression of Notch3 and Jagged2 is associated not only with gastric cancer development but also with the intestinal/glandular differentiation of gastric carcinoma cells, suggesting a role as a possible favourable prognostic indicator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 31 publications
(64 reference statements)
1
40
0
1
Order By: Relevance
“…However, the present data demonstrated that Notch 3 is (8,9,13). The mechanism of this phenomenon and how Notch 3 exerts its function in NSCLC remain unclear and require further research.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the present data demonstrated that Notch 3 is (8,9,13). The mechanism of this phenomenon and how Notch 3 exerts its function in NSCLC remain unclear and require further research.…”
Section: Discussionmentioning
confidence: 84%
“…In hematological malignancies, the role for Notch is well established, while more recent studies have demonstrated the significance of Notch activity in the initiation and progression of solid tumors (5)(6)(7)(8)(9). The mammalian Notch receptor family consists of four type I transmembrane receptors (known as Notch 1-4), all of which have been implicated in human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer cells, Notch1 and Notch2 pathways have been shown to promote tumorigenesis [4, 5]. Furthermore, Notch3 receptor expression was associated with gastric cancer development [6] and Notch4 receptor promoted gastric cancer growth [7]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, in patients with HCC an epithelial gene signature has been associated with sensitivity to the epidermal growth factor receptor inhibitors gefitinib and cetuximab (65). Deregulated expression of Notch, including the overexpression and activation of Notch proteins, ligands and targets, has been identified in numerous solid tumors, including cervical, endometrial, renal, lung and gastric carcinomas (66). These findings suggest that additional signaling pathways may affect whether Notch functions as a tumor suppressor or oncogene in a particular tissue (67).…”
Section: Role Of Notch In Hcc and Icc Developmentmentioning
confidence: 93%